Государственная политика в отношении населения старших возрастных групп - Kostenko A. A. (Students' scientific research and developments, 2017)
Population ageing and old age are the object of study of various branches of scientific knowledge, the global ageing of the world population caused by the need to develop universal policies for older citizens.
Keywords: социальная политика; пожилые люди; social policy; социальные программы; older people; нетрудоспособное население; ncapacitated persons; social programs